Genetic diagnosis of three intellectually disabled individuals in a pedigree and insights into fragile X syndrome diagnosis - Huang, Jianmei; Kang, Bing; Xia, Xiaoliang; Guo, Zhenglong; Lv, Yibing; Yang, Wenke; Wang, Chenyang; Wang, Jinming; Liao, Shixiu (Frontiers in Neuroscience, 2026)
Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability (ID). However, its diagnostic rate needs to be improved by screening for specific populations. Here, we determined the genetic cause of three ID patients in the affected pedigree and derived diagnostic insights for FXS. Enrolled at Henan Provincial People’s Hospital in April 2025, the family underwent multiple diagnostic tests. Whole-exome sequencing failed to detect causative variants—consistent with its inability to identify dynamic trinucleotide repeat expansions. Expanded pedigree analysis showed the inheritance did not fit typical autosomal dominant/recessive or X-linked models. This raised suspicion of FXS. Trinucleotide repeat primed PCR with capillary electrophoresis (TP-PCR/CE) confirmed proband III-1 as an FXS full-mutation individual, and comprehensive FXS analysis (CAFXS) validated this result while identifying counselee III-2 as a female pre-mutation carrier. All three ID cases harbored FMR1 full-mutation, with ID severity correlating with CGG repeat length. Notably, the maternal pre-mutation carrier (152 CGG repeats) had offspring with variable repeat dynamics: full-mutation (427 repeats) and reduced pre-mutation (71 repeats in III-2). These findings confirm FXS as the ID etiology and emphasize the clinical necessity of FXS-targeted screening in ID families with atypical inheritance patterns.